Mapping the Evolution of Sharia Financial Literacy and Behavior: A Bibliometric Analysis from 1990 to 2023 - Mukti, Titania (Review of Islamic Economics and Finance, 2024)
Purpose –The rapid development of research on Sharia financial literacy and financial behavior is not in line with the slow development of Indonesia's Sharia financial literacy index and Sharia financial behavior. Thus, it is necessary to conduct an evaluation that can map previous research and determine the direction of future research development. This study aims to determine the trend and direction of the development of Sharia financial literacy research and Sharia financial behavior and to identifying emerging trends in Sharia financial literacy and behavior.Methodology - The methodology used bibliometric analysis. This research uses 1990-2023 data with the keywords: financial literacy, Sharia financial literacy, sharia financial literacy, digital financial literacy, financial behavior, sharia financial behavior, Sharia financial behavior, investment behavior, saving behavior, sharia financial decisions, and financial decisions. Data searching with Indonesian and English in Google Scholar. Research analysis using VOSViewer.Findings - The results obtained 49,162 documents with 11 clusters of research trends in Sharia financial literacy and Sharia financial behavior. The author who contributed the most to producing works was Annamaria Lusardi, with 258 research documents. The most frequently used keywords are financial literacy, investment behavior, consumer behavior, and financial decision. The direction of research for future research developments can choose to use the keywords Sharia financial literacy, sharia financial literacy, digital financial literacy, saving behavior, consumer behavior, investment behavior, and sharia financial decisions. Keywords: Sharia Financial Literacy, Sharia Financial Behavior, Bibliometric Studies.